ANALISIS KECEMASAN SISWA DALAM PEMBELAJARAN DARING PADA KELAS XI MA ISLAMIYAH PONTIANAK TAHUN 2021 - Heni Mayasari; Indri Astuti; Luhur Wicaksono (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the results of the analysis of student anxiety in online learning in class XI MA Islamiyah Pontianak. The form of research uses a survey study, the population in this study is all students of class XI science and social studies totaling 31 students, the research method used is descriptive with a quantitative approach, data collection is an indirect communication technique using questionnaires distributed via google form, data analysis using percentage correction. The results showed that reality anxiety was 59% in the moderate category, 57% for neurotic anxiety was in the moderate category, and 55% for moral anxiety was in the medium category. Based on the description above, in general, the analysis of student anxiety in online learning is still moderate and not optimal in class XI MA Islamiyah Pontianak.Keywords: Analysis, Student Anxiety, Online Learning